Analysis of Readiness for Implementation of the Smart City Masterplan in Wonogiri Regency - Manggalou, Singgih; Uang, Yulinda; Azizatun, Binti; Bataha, Katerina (Publisher Cv. Inara, 2023)
The development of the world's digital governance era has reached the development of smart city 4.0. Not many cities can make that happen. In Indonesia, the movement towards smart cities is still starting to be echoed. So it is necessary to prepare and have the will of the region to implement a smart city because of the difficulty in preparing to implement a smart city. Wonogiri Regency is one of the districts selected for smart city implementation because the achievement of the Electronic-Based Government System (SPBE) indicator has increased. The purpose of this study was to analyze the readiness of implementing a smart city master plan in the Wonogiri Regency. This research is a qualitative type with data collection techniques through in-depth interviews with 8 purposively selected informants. The researcher found that the readiness of the five components (nature, structure, infrastructure, superstructure, and culture) was 51% in good condition, 32% in moderate condition, and 17% in poor condition. This means that it is necessary to increase the structural and superstructure components where conditions are still bad. Recommendations in increasing readiness for smart city implementation include making regional smart city policies; improving the quality of the relevant apparatus to improve the quality of ICT capabilities; increasing the amount of budget in the smart city program; and preparing supporting institutions